Providing feedback for students' drafts in academic writing: can developmental Rubric do the trick? - Md. Zamin, Ainul Azmin (Faculty of Languages and Communication, Universiti Sultan Zainal Abidin, 2015)
This case study aims to investigate the use of developmental rubric designed specifically for academic writing. In process writing, the drafting phase is a crucial stage where students are expected to improve their writing based from feedback provided by both teachers and peers. For the purpose of this qualitative study, a total of 4 classes were involved, with 13 informants interviewed. The developmental rubric was used in class for 2 drafting stages where students utilized it for peer feedback and also for self-editing. The construction of a much-needed developmental rubric to enhance students’ academic writing skills and to provide the necessary feedback during the writing process is crucial but careful consideration is required in several aspects. Overall, the teachers felt positive about the use of rubric as it helped them in their marking and it confirmed that they are on track in terms of teaching. Teachers were able to specifically pin-point the areas where students needed to improve their academic writing. Students who used the rubric for self-editing admitted that it was not easy to be self-critical but they were positive about the use of the rubric in class. Meanwhile, the students involved in peer editing did not only use the rubric to provide feedback for their friends but more importantly used it as a guideline for them to learn from others’ errors in academic writing. Useful suggestions from both students and teachers indicated that there are aspects such as timing on the use of the rubric, avoiding the use of difficult vocabulary, putting the rubric online and adding a section on APA technique, that were also recommended. Several implications were also discussed. The result from this study is used to develop a new approach to provide feedback in the teaching of English for Academic Writing (EAW) at tertiary level.